Pengaruh Myofascial Release Dan Stretching Terhadap Penurunan Nyeri Fasciitis Plantaris Pada Sales Promotion Girls Pengguna High Heels di Matahari Department Store Solo Square Surakarta - Septiani, Riza Mufti, Dwi Kurniawati SST.Ft.,M.Kes (2016)
Latar Belakang : Fasciitis plantaris is a condition of inflammation that results from the occurrence of overstretch in the Fascia plantaris. Plantaris (aponeurosis) fascia is fibers fibrosus of connective tissue that is derived from the medial calcaneus tuberosity runs longitudinally to the metatarsophalangeal joint medial longitudinal arkus forming in the legs. Research Objectives : to know how the granting of Myofascial Release and Stretching against a decrease in pain Fasciitis plantaris on Sales Promotion Girls High heels user PT. Matahari Square Solo, Surakarta Research Methods : This type of research is alphabets experiment, using the approach of Quasi alphabets experiment or pseudo alphabets experiment because all variables are not all controlled by researchers with the research design is a Pre and Post test with two Group design. The research results were analyzed using the SPSS program. Test of influence by using the Wilcoxon test while the test different influences using Mann Whitney Research Results : On the existence of the Group I the influence of Myofascial Release against a decrease in pain with significant value p = 0.006 (p < 0.05). While in Group II the presence of the influence of Stretching against a decrease in pain with significant value p = 0.002 (p < 0.05). On the influence of different test between Stretching and Myofascial Release obtained the value of p = 0.007 (p < 0.05). Conclusion : There is a significant influence on the awarding of myofascial release and stretching against a decrease in pain fasciitis plantaris. There is a difference significant influence between the granting of myofascial release with stretching against a decrease in pain fasciitis plantaris. Stretching is better in lowering a patient's pain fasciitis plantaris compared with Myofascial release.